2017
DOI: 10.1002/lno.10646
|View full text |Cite
|
Sign up to set email alerts
|

Responses of carbonate system and CO2 flux to extended drought and intense flooding in a semiarid subtropical estuary

Abstract: Globally, estuaries are considered important CO 2 sources to the atmosphere. However, estuarine water carbonate chemistry and CO 2 flux studies have focused on temperate and high latitude regions, leaving a significant data gap in subtropical estuaries. In this study, we examined water column carbonate system and airwater CO 2 flux in the Mission-Aransas Estuary, a subtropical semiarid estuary in the 21 and 2132.5 6 256.8 lmol kg 21 , TA was 2497.6 6 172.1 lmolÁkg 21 and 2333.4 6 283.1 lmol kg 21 , pCO 2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 69 publications
(90 reference statements)
2
30
2
Order By: Relevance
“…k). This is consistent with our previous study, which revealed that evaporating estuarine water holds less dissolved CO 2 ; and CO 2 efflux is significant under high wind speeds (Yao and Hu ). This CO 2 efflux should contribute to DIC loss (DIC estuarine < 0; Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…k). This is consistent with our previous study, which revealed that evaporating estuarine water holds less dissolved CO 2 ; and CO 2 efflux is significant under high wind speeds (Yao and Hu ). This CO 2 efflux should contribute to DIC loss (DIC estuarine < 0; Fig.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Chen et al () estimated that average CO 2 flux in North American estuaries is 2.2 mol·C·m −2 ·yr −1 , although their study was mostly based on U.S. east coast estuaries. Furthermore, annual CO 2 flux in MAE during these 3 years was 6.9 ± 6.5 mol·C·m −2 ·yr −1 ; our previous study estimated a much higher CO 2 flux in MAE (12.4 ± 3.3 mol·C·m −2 ·yr −1 ), although that study only spanned May 2014 to April 2015, a period of drought that preceded a large freshwater discharge event in April 2015 (Yao and Hu ). In the longer time series that we present in this study, it is likely that elevated freshwater inflow delivered nutrients and subsequently enhanced autotrophic production and reduced CO 2 emission, especially when MAE returned to an ocean‐dominated condition following the flooding.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Thus conceptually, higher freshwater inflow to Guadalupe, Nueces, and BB should lead to increased buffering capacity, whereas in Lavaca-Colorado the opposite occurred, with potential negative impacts on shellforming organisms in the system (Salisbury et al 2008;Mathis et al 2011). This finding highlights the important role that both watershed mineralogy and freshwater inflow play as drivers of estuarine carbonate chemistry (Yao and Hu 2017). On average, inorganic nutrient concentrations tended to be highest in upper San Antonio Bay, followed by Lavaca-Colorado, Nueces, and BB.…”
Section: Discussionmentioning
confidence: 86%